Antimicrobial Resistance Molecular Mechanisms of Helicobacter pylori in Jordanian Children: A Cross-Sectional Observational Study - Salma Burayzat; Mohammad Al-Tamimi; Mohammad Barqawi; Mustafa Sabri Massadi; Jumanah Abu-Raideh; Hadeel Albalawi; Ashraf I. Khasawneh; Nisreen Himsawi; Maha Barber (MDPI AG, 2023)
Background: H. pylori antimicrobial resistance causes increasing treatment failure rates among H. pylori gastritis in children. This study investigates the molecular mechanisms of H. pylori antimicrobial resistance among Jordanian children. Methods: Demographic, clinical, and laboratory data were recorded for children referred to Prince Hamzah Hospital. Clarithromycin, Metronidazole, and Levofloxacin susceptibility were tested via E-test. Clarithromycin-related mutations were investigated using Real-Time (RT)-PCR and Levofloxacin resistance was analyzed with DNA sequencing of the gyrA gene. Results: 116 children were recruited, including 55.2% females and 55.2% in the age range of 10.1 to 14 years. A total of 82.7% were naïve to eradication therapy. H. pylori positivity was 93.9%, 89.6%, 61.7%, and 84.3% according to Rapid Urease Test, histology, culture, and RT-PCR, respectively. Resistance rates were 25.9% for Clarithromycin, 50% for Metronidazole, and 6.9% for Levofloxacin via E-test. A2142G or A2143G or a combination of both mutations concerning Clarithromycin resistance were documented in 26.1% of samples, while mutations in gyrA gen-related to Levofloxacin resistance were reported in 5.3% of samples. Antibiotic resistance was significantly affected by abdominal pain, anemia, hematemesis, and histological findings (p < 0.05). Conclusion: H. pylori resistance was documented for Metronidazole and Clarithromycin. RT-PCR for H. pylori identification and microbial resistance determination are valuable alternatives for cultures in determining antimicrobial susceptibility.